1998
DOI: 10.1074/jbc.273.3.1788
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Regulation of Raf-1 and Mitogen-activated Protein Kinase (MAP) Kinase Kinases 1 and 2 by MAP Kinase Phosphatase-1 (MKP-1)

Abstract: Inactivation of growth factor-regulated mitogen-activated protein (MAP) kinases (ERK1 and ERK2) has been proposed to occur in part through dephosphorylation by the dual specificity MAP kinase phosphatase-1 (MKP-1), an immediate early gene that is induced by mitogenic signaling. In this study, we examined the effect of MKP-1 on signaling components upstream of ERK1 and ERK2. Coexpression of MKK1 or MKK2 with MKP-1 resulted in 7-10-fold activation of mitogen-activated protein kinase kinase (MKK), which required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 59 publications
1
48
1
Order By: Relevance
“…3), suggesting that MKP-1 is not regulating the age-related decrease in ERK-MAP kinase activity. Further support for the lack of a role for MKP-1 in regulating the decrease in ERK-MAP kinase comes from the work of Shapiro and Ahn (38). They reported that MKP-1 has a positive effect on Raf kinase activity independent of the basal inhibition of ERK-MAP kinase activity.…”
Section: Discussionmentioning
confidence: 86%
“…3), suggesting that MKP-1 is not regulating the age-related decrease in ERK-MAP kinase activity. Further support for the lack of a role for MKP-1 in regulating the decrease in ERK-MAP kinase comes from the work of Shapiro and Ahn (38). They reported that MKP-1 has a positive effect on Raf kinase activity independent of the basal inhibition of ERK-MAP kinase activity.…”
Section: Discussionmentioning
confidence: 86%
“…The Ras to Raf to MEK to MAPK pathway has been thought to be a simple linear pathway. Recently, COT1 has been shown to activate MEK (Hagemann et al, 1999), TC21 has been shown to activate Raf (Rosario et al, 1999), MKP-1 regulates c-Raf and MAPK (Shapiro and Ahn, 1998). Clearly there are`branches' in the pathway and it may be that other molecules may also participate in the MAPK cascade in ways that have not been observed to date.…”
Section: Discussionmentioning
confidence: 94%
“…Catalytically inactive dominant negative (DN) mutants of ERK1 (K71R) and ERK2 (K52R) cloned in pCEP4 vector (17) were provided by M. H. Cobb (University of Texas Southwestern Medical Center, Dallas). A constitutively active (CA) MEK1 and DN-MEK1 cloned in pCMV were described (18,19). Wild type, CA-MEKK1 (⌬367), and DN-MEKK1 (⌬367…”
Section: Methodsmentioning
confidence: 99%